How to Improve the Financial Oversight of Public Corporations - Allen, Richard (IMF How To Notes; How-To Note ;, 2016)
Many studies have highlighted how failures of public corporations (otherwise known as state-owned enterprises) can result in huge economic and fiscal costs. To contain the risks associated with these costs, an effective regime for the financial supervision and oversight of public corporations should be put in place. This note discusses the legal, institutional, and procedural arrangements that governments need to oversee the financial operations of their public corporations, ensure accountability for their performance, and manage the fiscal risks they present. In particular, it recommends that governments should focus their surveillance on public corporations that are large in relation to the economy, create fiscal risks, are not profitable, are unstable financially, or are heavily dependent on government subsidies or guarantees.